Modulating the electron structure of Co-3d in Co3O4−x/WO2.72 for boosting peroxymonosulfate activation and degradation of sulfamerazine: Roles of high-valence W and rich oxygen vacancies - Yang, Xudong; Duan, Jun; Juanjuan Qi; Xiuze Li; Gao, Jing; Yifei Liang; Si Li; Tao Duan; Liu, Wen (Journal of Hazardous Materials, 2023)
Sulfate radical (SO4•–)-based heterogonous advanced oxidation processes (AOPs) show promising potential to degrade emerging contaminants, however, regulating the electron structure of a catalyst to promote its catalytic activity is challenging. Herein, a hybrid that consists of Co3O4−x nanocrystals decorated on urchin-like WO2.72 (Co3O4−x/WO2.72) with high-valence W and rich oxygen vacancies (OVs) used to modulate the electronic structure of Co-3d was prepared. The Co3O4−x/WO2.72 that developed exhibited high catalytic activity, activating peroxymonosulfate (PMS), and degrading sulfamerazine (SMR). With the use of Co3O4−x/WO2.72, 100 % degradation of SMR was achieved within 2 min, at a pH of 7, with the reaction rate constant k1 = 3.09 min−1. Both characterizations and density functional theory (DFT) calculations confirmed the formation of OVs and the promotion of catalytic activity. The introduction of WO2.72 greatly regulated the electronic structure of Co3O4−x. Specifically, the introduction of high-valence W enabled the Co-3d band centre to be closer to the Fermi level and enhanced electrons (e–) transfer ability, while the introduction of OVs-Co in Co3O4−x promoted the activity of electrons in the Co-3d orbital and the subsequent catalytic reaction. The reactive oxygen species (ROS) were identified as •OH, SO4•–, and singlet oxygen (1O2) by quenching experiments and electron spin resonance (EPR) analysis. The DFT calculation using the Fukui index indicated the reactive sites in SMR were available for an electrophilic attack, and three degradation pathways were proposed.
Keywords: CoO; Oxygen vacancies (OVs); Peroxymonosulfate (PMS); Sulfamerazine (SMR); WO